PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR DINAS PENDIDIKAN KOTA CIMAHI : Survey terhadap PNS Dinas Pendidikan Kota Cimahi - Rohendi, Eek (2010)
The research objective was to determine the influence of work motivation and work environment variables to employee performance. In this study determined that respondents were 61 person staff in the Office of Environmental Education Cimahi. Further analysis of data using multiple linear regression analysis and hypothesis testing through analysis of the ttest and ftest. Based on the analysis and discussion of motivations known to significantly influence the performance of employees with the obtained value ttest>ttable (2.904>2.00) and the work environment significantly influence the performance of employees with the obtained value of ttest>ttable (10.280>2.00) and between motivation and work environment significantly influence the performance, with the obtained value of Ftest> Ftable (52.119>4.00) and a smaller probability of 0.05. Based on these findings, researchers tried to give contributions is to improve employee performance Cimahi Education Department's office, it needs to be maintained and even improved employee motivation to properly meet the needs of the employees are always so enthusiastic and passionate in the work. Organizations are expected to consider the working environment both physical and social aspects, this is because whatever job without supported by conducive working environment will not result in the maximum of job execution. Create a work environment that can enhance employee creativity by striving to always improve employee knowledge, improve skills of employees are all owned, striving for the promotion for employees who perform well and trying to mutation for the officials who occupy a position of more than five years.